2009
DOI: 10.1007/s11743-009-1147-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Scale Formed on the Surfaces of Toilet Bowls

Abstract: Repeated use of a toilet results in the build-up of a deposit derived from urine and hard water on the surface of the toilet bowl. The hardened mineral scale is difficult to clean completely, especially in the case of deposits under the rim. A number of studies have focused on kidney stones, which are also caused by urine in the urinary tract; little attention, however, has been paid to the detailed composition and structure of the toilet scale. To develop powerful products for removing the toilet scale effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…1,2 Urea hydrolysis via the urease enzyme is also the cause of operating problems with urine-diverting toilets and nonwater urinals. [3][4][5][6][7] The reaction involves urea, an abundant compound found in the environment and human urine, 8 hydrolyzing to form ammonia and bicarbonate resulting in an elevated pH of the surrounding soil or solution. 9 Hydrolysis requires the urease enzyme, which is a metalloenyzme with two nickel ions per catalytic unit in the active site.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Urea hydrolysis via the urease enzyme is also the cause of operating problems with urine-diverting toilets and nonwater urinals. [3][4][5][6][7] The reaction involves urea, an abundant compound found in the environment and human urine, 8 hydrolyzing to form ammonia and bicarbonate resulting in an elevated pH of the surrounding soil or solution. 9 Hydrolysis requires the urease enzyme, which is a metalloenyzme with two nickel ions per catalytic unit in the active site.…”
Section: Introductionmentioning
confidence: 99%
“…14 Urine diversion processes are susceptible to the urea hydrolysis reaction due to urine's high urea content, and the ubiquitous presence of bacteria and bacterial urease on bathroom fixtures and on the human body. 3,5,17 Urea hydrolysis in urine diversion systems is especially detrimental due to the formation of calcium and magnesium phosphates that form after hydrolysis has occurred in the urinals, pipes, and storage tanks of undiluted urine. 4,5,9 The precipitates that form are hard minerals that are not easily removed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The urease enzyme is produced by a wide range of organisms, from eukaryotes to prokaryotes, and is most active as the bacterial urease in wastewater collection systems. , The addition of ammonia, bicarbonate, and hydroxide via urea hydrolysis raises the pH of fresh urine from pH 6 to pH 9 and creates supersaturated conditions for precipitation of phosphate minerals, such as struvite (NH 4 MgPO 4 ·6H 2 O) and hydroxyapatite (Ca 5 (PO 4 ) 3 (OH)). ,, A study on scale formation on conventional flush toilets bowls found that 65% of the scale was due to the precipitation of struvite, calcium phosphate, and calcium carbonate, with the remaining 45% of scale being organic-based solids . Research on urine diversion systems has indirectly investigated urea hydrolysis by studying the rate, extent, and type of minerals that precipitate in urine. ,, Previous research that has directly investigated the urea hydrolysis reaction and its inhibition is mostly from soil science and microbiology. According to Ray et al, urea hydrolysis inhibitors most commonly found in soil science literature were not able to inhibit urea hydrolysis in urine due to the presence of competing ions .…”
Section: Introductionmentioning
confidence: 99%
“…18,20,21 A study on scale formation on conventional flush toilets bowls found that 65% of the scale was due to the precipitation of struvite, calcium phosphate, and calcium carbonate, with the remaining 45% of scale being organic-based solids. 22 Research on urine diversion systems has indirectly investigated urea hydrolysis by studying the rate, extent, and type of minerals that precipitate in urine. 18,23,24 Previous research that has directly investigated the urea hydrolysis reaction and its inhibition is mostly from soil science and microbiology.…”
mentioning
confidence: 99%